Kompetitive Allele Specific PCR (KASP) Markers for Potato: An Effective Tool for Increased Genetic Gains - Moctar Kante; Hannele Lindqvist-Kreuze; Leticia Portal; Maria David; Manuel Gastelo (Agronomy, 2021)
Potato virus Y (PVY) and Phytophthora infestans (Mont.) de Bary that causes potato late blight (LB), pose serious constraints to cultivated potatoes due to significant yield reduction, and phenotyping for resistance remains challenging. Breeding operations for vegetatively propagated crops can lead to genotype mislabeling that, in turn, reduces genetic gains. Low-density and low-cost molecular marker assessment for phenotype prediction and quality control is a viable option for breeding programs. Here, we report on the development of kompetitive allele specific PCR (KASP) markers for LB and PVY resistance, and for routine quality control assessment of different breeding populations. Two KASP markers for LB resistance and two for PVY Ryadg were validated with an estimated assay power that ranged between 0.65 and 0.88. The developed QC KASP markers demonstrated the capability of discriminating tetraploid calls in breeding materials, including full-sibs and half-sibs. Routine implementation of the developed markers in a breeding program would assist with better allocation of resources and enable precise characterization of breeding material, thereby leading to increased genetic gains.